Relative age effect in Spanish association football: Its extent and implications for wasted potential - Prez Jimnez, I.; Pain, M. T. G. (Journal of Sports Sciences, 2008)
Spain is one of the largest and most successful powers in international youth football, but this success has not extended to the national team. This lack of continued success seems to indicate a loss of potential. The relative age effect has been detected in football in many countries. Understanding the extent of this bias in the youth teams of Spanish elite clubs may help to improve selection processes and reduce the waste of potential. Comparisons between players from: the Spanish Professional Football League, all age categories of these clubs' youth teams, the Under-17 to Under-21 national teams, the national team, and the Spanish population, show a constant tendency to under-represent players from the later months of the selection year at all age groups of youth and Under-17 to Under-21 national teams. Professional and national team players show a similar but diminished behaviour that weakens with ageing, which suggests that talent identification and selection processes can be improved to help better identify potential talent early on and minimize wasted potential.